Comparison of Surgical Techniques for Correction of Mandibular Asymmetry in TMJ Ankylosis Patients - Samir Mansuri; S. Hemavathy; Annaluru Sri Sasank Tejaswee; Lakshmi Manasa Pappu; Harvey Thomas; Lipsa Bhuyan; Sunil Kumar Gulia (Wolters Kluwer Medknow Publications, 2024)
Background: Temporomandibular joint (TMJ) ankylosis frequently results in mandibular asymmetry, which impairs an affected person's ability to function and look good. Because of the intricacy of TMJ ankylosis and the variety of surgical procedures available, correcting mandibular asymmetry surgically can be difficult. Methods: Patients with mandibular asymmetry and TMJ ankylosis who had surgery at a tertiary care facility between certain periods were the subject of a retrospective investigation. Medical records were used to gather information on patient demographics, pre-operative imaging, surgical methods, and post-operative results. Surgical methods included condylectomy with or without reconstruction, joint reconstruction with or without orthognathic surgery, and unilateral or bilateral mandibular distraction osteogenesis (MDO). Occlusion, patient-reported results, and facial symmetry made up the evaluation criteria. Findings: The study had a total of 50 patients, with different surgical method distributions. Comparing unilateral and bilateral MDO to condylectomy and joint reconstruction, notable gains in face symmetry and occlusion were seen. The largest complication rate was seen with condylectomy, mostly from recurrence and device-related issues, albeit the rates of other procedures varied as well. Conclusion: In conclusion, customized treatment planning is necessary for the correction of mandibular asymmetry in individuals with TMJ ankylosis. Although mandibular distraction osteogenesis produces better results for occlusion and facial symmetry, it is crucial to carefully weigh the risks involved. While still feasible treatments, condylectomy and joint reconstruction require strict monitoring for any consequences. In order to enhance patient care in this difficult patient group, future research should concentrate on improving treatment procedures and long-term results.